The advantages of our studies - Frost, John (My University, 1892)
Introduction: “Well what do you learn at college, anyway?” is the query often put to the college student by his friends at home. He attempts to explain, but is soon convinced of his inability to express definitely and completely the training that his college provides. He can name every study in the course. This, indeed, throws much light on the subject; but not enough. For it gives but a slight hint of the real practical good of the college in furnishing to the student experience, information, and discipline. In considering the course of instruction at our college, we must bear in mind the object aimed at. Our institution is not a university, a classical college, a normal school, a technical institute, or an academy, but is as its name indicates an agricultural college. It is one of the many agricultural colleges of our country created by an act of Congress in 1862. This act provided for the support of at least one college in eat state where the leading object should be, “without excluding other scientific and classical studies, and including military tactics, to teach such branches of learning as are related to agriculture and the mechanic arts”. So it is to be seen that ours is a peculiar, or particular, kind of college known in our country during only the last few decades.
Citation: Frost, John. The advantages of our studies. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: College; Agriculture; University; Advantage; Education; Theses; Manuscripts (documents)